2001
DOI: 10.1136/heart.86.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the pulmonary veins: relevance to radiofrequency ablation

Abstract: Background-Radiofrequency ablation of tissues in pulmonary veins can eliminate paroxysmal atrial fibrillation. Objective-To explore the characteristics of normal pulmonary veins so as to provide more information relevant to radiofrequency ablation. Methods-20 structurally normal heart specimens were examined grossly. Histological sections were made from 65 pulmonary veins. Results-The longest myocardial sleeves were found in the superior veins. The sleeves were thickest at the venoatrial junction in the left s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
330
5
7

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(368 citation statements)
references
References 17 publications
26
330
5
7
Order By: Relevance
“…[1][2][3] Therefore, electrical isolation of these ostia by catheter ablation is presently used as a treatment modality for patients with this problem. This isolation can be achieved by discrete lesions at the rim of the ostium, guided by perimetric mapping with a multipolar loop catheter like the Lasso (Biosense Webster, Inc) or by lesions in the left atrium encircling multiple PV ostia.…”
mentioning
confidence: 99%
“…[1][2][3] Therefore, electrical isolation of these ostia by catheter ablation is presently used as a treatment modality for patients with this problem. This isolation can be achieved by discrete lesions at the rim of the ostium, guided by perimetric mapping with a multipolar loop catheter like the Lasso (Biosense Webster, Inc) or by lesions in the left atrium encircling multiple PV ostia.…”
mentioning
confidence: 99%
“…Less radiofre- quency energy is needed to isolate the right inferior pulmonary vein because there is less muscle surrounding this vein than the other pulmonary veins. 2,3 During follow-up, a repeat ablation procedure was performed in 11% of patients. Among the 176 patients with paroxysmal AF, the proportion who were free of recurrent AF in the absence of antiarrhythmic drug therapy was 72% at 12 months, and 70% at 24 months.…”
Section: Results Of Segmental Ostial Ablationmentioning
confidence: 99%
“…2,3 Although the underlying mechanisms are still unclear, the muscle within these sleeves may be arrhythmogenic. [4][5][6] There are at least 3 possible ways that the pulmonary veins may contribute to the generation of AF.…”
Section: Role Of Pulmonary Veins In Atrial Fibrillationmentioning
confidence: 99%
“…Histological sections from PVs have demonstrated the high variability of myocardial architecture in the PVs. 33 The presence of gaps in the myocardial sleeves, and acquired areas of fibrosis (Fig. 3), suggests that ablation of the entire circumference of PV ostia may not be necessary and may only serve to increase the adverse effects.…”
Section: Segmental Isolation Of Pulmonary Veinsmentioning
confidence: 99%
“…It has been postulated that, with the anatomical arrangement of longitudinal fascicles, a focal lesion placed at the venoatrial junction will eliminate venous potentials detected distally. 33 Haïssaguerre et al have shown that PV isolation can be achieved by selective ablation of ostial sites where a PV potential is recorded. 34 Selective ablation of ostial sites where a PV potential is recorded provides an unambiguous endpoint and has the advantage of not requiring detailed mapping of spontaneous ectopy, as ostial PV potentials can be recorded during sinus rhythm or atrial pacing.…”
Section: Segmental Isolation Of Pulmonary Veinsmentioning
confidence: 99%